Evaluation of dental fear in children with and without dental trauma experience by using CFSS-DS questionnaire - Ivančić Jokić, Nataša; Majstorović, Martina; Bakarčić, Danko Szirovica, Lajozs; Zarevski, Predrag (2008)
The paper shows the results of evaluation of dental fear in childeren with and without dental trauma expirience. CFSS-DS questionnaire is used.
ENG